Fluid Resuscitation Aggravates the Cellular Injury in a Hemorrhagic Shock Model - Kubra Vardar; Kubra Can; Ugur Aksu (Dubai Medical Journal, 2022)
Background: Resuscitation is the initial step for hemorrhagic shock. However, there is still controversy as to which fluid achieves the best results clinically and experimentally. Aim: It was aimed to investigate the effects of 0.9% NaCl (sodium chloride) and 6% HES (hydroxyethyl starch) on the kidney and blood environment. Methods: Twenty-four male Wistar rats were assigned as control, shock, and resuscitated (colloid: 6% HES and crystalloid: 0.9% NaCl) groups. Besides hemodynamics (mean arterial pressure and shock index) monitoring and kidney function evaluation, hemolysis, oxidative stress, inflammation, and glycocalyx degradation were evaluated in the plasma and kidney. Results: (1) Macrohemodynamics were successfully restored by both fluids. (2) Although 3 times more crystalloid volume was applied compared to the colloid resuscitation, similar hematocrit levels were found in both resuscitation strategies (32.8 ± 2.3 vs. 33.3 ± 1.0). (3) NaCl resuscitation led to increases in the hemolytic index, catalytic iron, and sialic acid compared to control, while HES administration increased the levels of malondialdehyde, ischemia-modified albumin, and sialic acid. (4) However, both fluid resuscitation strategies could inhibit inflammation and oxidative stress in the kidney and restore kidney function parameters. Conclusion: Although both NaCl and HES resuscitation showed protection of the kidney function against oxidative stress and inflammation, these fluids initiated the injury process.